Redeeming time : Protestantism and Chicago's eight-hour movement, 1866-1912 - Mirola, William A. (William Andrew) (Working class in American history., 2015)
"During the struggle for the eight-hour workday and a shorter workweek, Chicago emerged as an important battleground for workers in "the entire civilized world" to redeem time from the workplace in order to devote it to education, civic duty, health, family, and leisure. William A. Mirola explores how the city's eight-hour movement intersected with a Protestant religious culture that supported long hours to keep workers from idleness, intemperance, and secular leisure activities. Analyzing how both workers and clergy rewove working-class religious cultures and ideologies into strategic and rhetorical frames, Mirola shows how every faith-based appeal contested whose religious meanings would define labor conditions and conflicts. As he notes, the ongoing worker-employer tension transformed both how clergy spoke about the eight-hour movement and what they were willing to do, until intensified worker protest and employer intransigence spurred Protestant clergy to support the eight-hour movement even as political and economic arguments eclipsed religious framing. A revealing study of an era and a movement, Redeeming Time illustrates the potential--and the limitations--of religious culture and religious leaders as forces in industrial reform"--